BUSINESS DEVELOPMENT OF HONEYGUIDE RESTO CAFé: AN ACTION RESEARCH APPROACH ON CAFé'S OPERATIONS - Abdulrahim, Ahmad M. Natsir; Lantu, Donald Crestofel (The Indonesian Journal of Business Administration, 2015)
Abstract.Since its establishment in June 2013, Honeyguide could only generate low income. Most of its customers are students and academic staffs of Faculty of Social and Political Sciences (FISIP), University of Indonesia, Depok and surrounding faculties.This research, conducted from June 2013-November 2014, used action research approach. As the action research approach input, this research used situational and internal analysis to determine Honeyguideâ??s root causes. The identified root causes were inadequate Standard Operating Procedure, lack of inventory control, lack of training program for employees, lack of alternative serving methods, and campusâ?? holiday schedule. By solving these root causes, it is expected that Honeyguide would become a sustainable business.The research itself consists of four cycles: entering the market, market assessment, cost optimization, and franchise initiation. Each cycle consists of planning, action, results, and reflection activities. During reflection activities, this research compares the action results with existing theory.From the research, it was discovered that customers seating time was relatively high. Management also considered current serving time too long. Therefore, both led to low income.The proposed implementation plan is that Honeyguide management will conduct the concurrent research in a 6-months periodic basis. The concurrent research may help Honeyguide management to develop alternative method for serving, evaluate seating time, and develop adequate Standard Operating Procedures (SOP) and training system for the employees while aiming to become a reputable franchise.Keywords: business development, action research, operations management, food and beverages industry